Impact of foreign exchange currencies towards Malaysian stock market (Kuala Lumpur composite index) / Wan Mohd Nursyakirin Wan Mohd Tarmizi - Wan Mohd Tarmizi, Wan Mohd Nursyakirin (Faculty of Business Management, 2017)
The objective of this paper is to investigate the impact of foreign exchange currencies towards Malaysian stock market which means Kuala Lumpur Composite Index (KLCI). This study will focus on Kuala Lumpur Composite Index (FBMKLCI) stock price movement. The factors that may influence the stock market price will be observer closely. The dependent variable for this research is Kuala Lumpur Composite Index (KLCI). While the 5 independent variables that has been selected are foreign exchange rates of United States (USD), Japan (JPY), Canada (CAD), Great Britain (GBP) and European Union (EU). The data that has been taken are pooled for 10 years (January 2007 – November 2016). The data is from quarterly data from those years. Total number of observations is 38. The data was obtained from Datastream. This study used quantitative secondary data which is time series data and multiple regression model represented by the ordinary least squares (OLS). It involves the Malaysian stock price index as dependent variable and the independent variables are USD, JPY, CAD, GBP and EU. The result of this data has been revealed that only USD, JPY and EU have significant relationship with the Malaysian stock market itself while the other two variables CAD and GBP do not have significant relationship with the KLCI.